The Impact of Human Development on Economic Growth: Evidence From Asean-4 Countries - Nur Sahfila Aloysius; Jaratin Lily; Chew Tze Cheng @ Nur Alesha Chew; Mohd. Rahimie Abd. Karim (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
This paper aims to determine the impact of human development on economic growth in ASEAN-4 countries, namely Malaysia, Indonesia, Thailand, and the Philippines. The analysis is based on data spanning the period from 1990 to 2021. The study employed the Human Development Index (HDI) as a proxy for human development, with GDP per capita as the dependent variable. Trade openness and foreign direct investment (FDI) were included as control factors. The present study applied Autoregressive Distributed Lag (ARDL) approach to examine the long run and short run relationships among the studied variables. The finding indicated evidence of cointegration among the variables across all sample countries. The results also showed mixed evidence on the long run and short run impacts of human development trade openness, and FDI on economic growth. The study key findings suggested the existence of a positive and significant long-run impact of human development on economic growth in Malaysia and Indonesia. Meanwhile, there is evidence of a short run effect between human development and economic growth for the whole sample of countries. In addition, trade openness and FDI showed evidence of a long run between Indonesia and Thailand. In the short run, trade openness is significant in Malaysia, the Philippines, and Thailand, while FDI is significant only in Indonesia. This study concludes that the factors that influence economic growth are country dependence and human development, which is considered an important factor in economic planning. Therefore, it was suggested that greater emphasis be placed on developing human capabilities in all fields.